Evaluation Of The Implementation Of The Sekolah Penggerak Program: A Case Study Of Smpn 3 South Tangerang - Ramadhan, Ramadhan; Juwono, Vishnu (International Journal of Social Service and Research, 2025)
This study aims to evaluate the implementation of the Driving School Program (PSP) at SMPN 3 South Tangerang. The research uses a qualitative approach with in-depth interview techniques with teachers as key informants. The results of the study show that the main challenges in the implementation of PSP are the gap in students' learning abilities and motivation as well as the need for teachers to adjust to curriculum changes. Training and assistance from the education office have been proven to help teachers in aspects of assessment, differentiation, and learning innovation, although limited digital facilities are still an obstacle. The effectiveness of PSP can be seen from the ability of teachers to conduct diagnostic assessments, design differentiated learning, and encourage creativity and active participation of students. The positive impact of this program includes creating a conducive learning atmosphere, increasing students' courage to speak up, and teachers' expectations for schools to become successful driving school models. The analysis using the CIPP evaluation model shows that PSP is relevant to the school context, supported by adequate input, runs through an adaptive process, and produces positive learning products. These findings show that PSP contributes to improving the quality of learning, but the sustainability of the program requires improving facilities, continuous mentoring, and strengthening the digital literacy of teachers and students.